2016
DOI: 10.3747/co.23.3051
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Pretreatment Circulating Neutrophils, Monocytes, and Lymphocytes on Outcomes in Lung Stereotactic Body Radiotherapy

Abstract: PurposeIn the present study, we determined the association of pretreatment circulating neutrophils, monocytes, and lymphocytes with clinical outcomes after lung stereotactic body radiotherapy (sbrt).Methods All patients with primary lung cancer and with a complete blood count within 3 months of lung sbrt from 2005 to 2012 were included. Overall survival (os) was calculated using the Kaplan-Meier method. Factors associated with os were investigated using univariable and multivariable Cox proportional hazards re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 31 publications
3
16
0
Order By: Relevance
“…A few studies have suggested that such a decline post SBRT for lung cancer could be due to irradiation of the bone marrow in the thoracic vertebral bodies [24], [25] or due to exposure of large pools of blood in the heart or great vessels to low dose radiation [26]. Higher NLR and PLR have been associated with poor outcomes as seen in various studies [16], [27], [28]. Interestingly, our study did not show association of pre-SBRT NLR or PLR with any survival end points on multivariate model which has been seen in another study as well [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies have suggested that such a decline post SBRT for lung cancer could be due to irradiation of the bone marrow in the thoracic vertebral bodies [24], [25] or due to exposure of large pools of blood in the heart or great vessels to low dose radiation [26]. Higher NLR and PLR have been associated with poor outcomes as seen in various studies [16], [27], [28]. Interestingly, our study did not show association of pre-SBRT NLR or PLR with any survival end points on multivariate model which has been seen in another study as well [29].…”
Section: Discussionmentioning
confidence: 99%
“…However, most of these studies have evaluated patients with advanced stage or medically operable early stage NSCLC who underwent surgery. There are very few studies evaluating their role in stage I NSCLC undergoing SBRT [15] , [16] . Most of these studies have limited their blood values measured within the 3 month period prior to initiating therapy [9] , [10] , [11] , [12] , [13] , [15] , [17] .…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, a retrospective study by Cannon also indicated elevated NLR and PLR were associated with poor survival 24 . Giuliani et al demonstrated that NLR and LMR were independently correlated with OS in early stage NSCLC patients who were treated with SABR 25 . In the present work, we combined the NLR, PLR, and LMR metrics in order to analyze their collective contribution to OS.…”
Section: Discussionmentioning
confidence: 99%
“…For localized NSCLC patients treated with SBRT, we hypothesize that NLR is predictive of competing mortality risk given our data. Giulani et al reported similar findings of no association with lung cancer-specific outcomes when analyzing NLR as a continuous variable [36]. This suggests an underlying propensity for mortality in the elevated NLR cohort.…”
Section: Discussionmentioning
confidence: 84%